2003
DOI: 10.1128/jvi.77.9.5339-5351.2003
|View full text |Cite
|
Sign up to set email alerts
|

The Pseudorabies Virus UL11 Protein Is a Virion Component Involved in Secondary Envelopment in the Cytoplasm

Abstract: Homologs of the small tegument protein encoded by the UL11 gene of herpes simplex virus type 1 are conserved throughout all herpesvirus subfamilies. However, their function during viral replication has not yet been conclusively shown. Using a monospecific antiserum and an appropriate viral deletion and rescue mutant, we identified and functionally characterized the UL11 protein of the alphaherpesvirus pseudorabies virus (PrV). PrV UL11 encodes a protein with an apparent molecular mass of 10 to 13 kDa that is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
160
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 95 publications
(167 citation statements)
references
References 40 publications
7
160
0
Order By: Relevance
“…Further, the HSV type 2 UL56 protein, a protein with significant similarities to the PRV Us9 type II-anchored membrane protein (3), has also been shown to be raft associated (24). Recently, it has been shown that the PRV UL11 tegument protein is membrane associated and is a diacylated protein, a hallmark of many raft-associated proteins, and may therefore be raft associated (23). Together with our present data, this indicates that many alphaherpesvirus membrane (glyco)proteins and tegument proteins may interact with lipid rafts, in different ways and with different affinities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the HSV type 2 UL56 protein, a protein with significant similarities to the PRV Us9 type II-anchored membrane protein (3), has also been shown to be raft associated (24). Recently, it has been shown that the PRV UL11 tegument protein is membrane associated and is a diacylated protein, a hallmark of many raft-associated proteins, and may therefore be raft associated (23). Together with our present data, this indicates that many alphaherpesvirus membrane (glyco)proteins and tegument proteins may interact with lipid rafts, in different ways and with different affinities.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it is known that proteins, such as Fc gamma receptors, can be indirectly raft associated through their affinity for other raft-associated proteins (16). Importantly, since lipid raft formation and protein association with lipid rafts occur in the Golgi complex (14), such a putative glycoprotein and tegument protein concentrating function of lipid rafts may also be significant for efficient alphaherpesvirus budding and particle formation, as has been hypothesized recently (17,23,26). In this context, it is interesting that lipid rafts have recently been shown to serve as budding platforms for several enveloped viruses, such as human immunodeficiency virus, Ebola virus, influenza virus, and measles virus (1,28,35,36,40), and that such lipid raft-mediated budding has been hypothesized to explain pseudotyping of different viruses, including HSV (37).…”
Section: Vol 78 2004 Lipid Raft Association Of Prv Glycoproteins 5285mentioning
confidence: 99%
“…Binding of these or other PrV or HSV-1 proteins to dynein implies redundancy in VPs available for retrograde transport, which is not surprising for such an important stage during viral replication. There are precedents for functional redundancy in other HSV-1 and PrV proteins [71,72].…”
Section: Dynein Cofactor: Dynactinmentioning
confidence: 99%
“…The variables which might explain these findings, include differences between the two alphaherpesviruses, different types of neurons, different peak kinetics of transport or technical differences. Although both of the herpesviruses share similar mechanisms of retrograde transport and might be expected to demonstrate similar mechanisms of anterograde transport, the two viruses show around 30% protein sequence homology (based on the comparison of structural proteins [59,72,108] Latest suggested explanation for the presence of enveloped capsids in axons is that envelopment of (HSV) virions occurs within varicosities (as shown by the presence of partially enveloped virions) [90] Separate HSV capsid and glycoprotein antigen in regions of axons between varicosities and growth cones versus co-transport in axons of PrV capsid and glycoprotein antigens…”
Section: Anterograde Axonal Transport Of Enveloped Pseudorabies Virionsmentioning
confidence: 99%
“…Immunoblot analysis of purified PrV-DUL11 or PrV-DUL16 virions that had been propagated on pUL11-or pUL16-expressing recombinant cells, respectively (RK13-UL11, RK13-UL16 in Fig. 2d; Kopp et al, 2003;Klupp et al, 2005a) showed that the pUL36 N-terminal fragment was not incorporated into virus particles after phenotypic complementation of PrV-DUL11 and PrV-DUL16, although it was well expressed in the respective infected cells (Fig. 2e).…”
mentioning
confidence: 99%